The adoption of poka-yoke mechanism towards reducing the incident of un-lifted side stand of motorcycle - Sahat, Muhammad Asyraf; Jamian, Rahim; Abdul Shukor, Jum’azulhisham (Universiti Tun Hussein Onn Malaysia, 2020)
In recent years, human mistake related road traffic accident caused by un-lifted side stand of motorcycle is receiving much attention. However, the existing design improvement efforts to tackle the problem are more likely towards complex design and applicable to limited variants. This research attempts to produce a prototype model of safety mechanism through the adoption of Poka-yoke (human mistake proofing) approach in reducing the incident of un-lifted side stand. The proposed design comprised side stand, gear lever, spring and sensor, which is based on side stand specification of Yamaha 125ZR model. The design employed stainless steel as main material, finite element analysis (FEA) method for validation of strength, bench working and arc welding as fabrication and assembly process, and functional testing for automatic retraction analysis. The results ascertained the side stand is automatically retracted without touching by the rider when gear lever is pushed. The findings revealed the adoption of Poka-yoke mechanism is effective to prevent human mistakes and carelessness, subsequently avoiding the road accidents caused by the un-lifted side stand. Recommendations are also highlighted for further development including the use of alternative material and multiple design.